DEGRADATION OF HUMIC ACID BY FLOATING PHOTOCATALYST TiO2/Cu-ARECA FIBER - Sugandi, Didiek; Agustiawan, Deri; Wijayanto, Ericco; Marpaung, Maria Oktavia Putri; Ayyash, Muhammad Yahya; Wahyuni, Nelly (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
The photocatalyst method is effective in degrading humic acid into O2 and H2 compoundsthat are more environmentally friendly. The photocatalysis process involves light andsemiconductors such as TiO2 to accelerate the reaction rate. Therefore, modification of TiO2is needed to shift light absorption to visible light by using Cu2+ doping and areca fiber. XRDcharacterization shows that Merck's TiO2 has shifted at 2Î¸, indicating that Cu has enteredthe TiO2 structure, and several peaks have reduced in intensity after being embedded withareca fiber, indicating that TiO2/Cu has successfully attached to areca fiber. FTIR resultsshow that TiO2/Cu has been attached to the areca fiber, which is marked by shifting andweakening the intensity of the Ti-O-Cu wave number absorption. The test results show thatTiO2/Cu embedded in areca fiber had higher degradation activity than TiO2/Cu withoutembedded, with a percent degradation of 54% for 180 minutes of irradiation. These resultsprove that TiO2/Cu floated to the surface of the solution can optimize irradiation so that itis effective in the degradation process.